Fabrication of quercetin nanoparticles by anti-solvent precipitation method for enhanced dissolution - Judeh, Zaher M. A. (2013)
The aim of this study was to enhance the dissolution rate of a poorly water-soluble drug quercetin by fabricating its nanoparticles with anti-solvent precipitation using the syringe pump and to investigate the effect of drug concentration, solvent to anti-solvent (S/AS) ratio, stirring speed and flow rate on the particle size. Characterization of the original quercetin powder and nanoparticles made by syringe pump was carried out by the scanning electron microscopy (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and dissolution tester. The results indicated that decreasing the drug concentration, increasing the stirring speed, flow rate and the S/AS volume ratio favoured the reduction in the particle diameter to ∼ 170 nm. Percent dissolution efficiency (%DE); relative dissolution (RD); mean dissolution time (MDT); difference factor (f1) and similarity factor (f2) were calculated for the statistical analysis. The dissolution of the drug nanoparticles was significantly higher compared with the pure drug in simulated intestinal fluid (SIF, pH 6.8).